Improving the level of historical education: Rome and the Etruscans - Mihajlovna Shmeleva, Liudmila (2021)
The aim of this article is to dominate the educational aspects of historical level by examining the relationship between Rome and the Etruscan cities of Veii and Caere. Rome and Veii fought constant wars for control of the trade routes passing through the Tiber and its tributaries, which was necessary for the development of both states. In this struggle, Rome and Veii sought allies for themselves both among the Etruscans and among the Latins. Ultimately, Rome won over the Veii in 396 BC, thus the Roman tribes were founded on the land of the Veii, and the city fell into desolation. The relations with Caere developed in a different way, since there were no economic contradictions between the Romans and the Caerites. The relations were built on a peaceful basis, and Caere even helped the Romans during the Gallic invasion at the beginning of the 4th century BC: they received part of the population who fled from Rome, and their shrine, which was most important for the Romans. At the same time, Roman expansion at the end of the 5th - 4th centuries BC. Led to the war between Rome and Caere, after which the Etruscan city was subordinated to Rome. The results of such research, above all, highlight the need to increase the level of educational knowledge in the field of history